EFFECTIVITY OF INDONESIAN HONEY ON DIABETIC FOOT ULCERS HEALING PROCESS: OBSERVATIONAL CASE STUDY: DOI: https://doi.org/10.35654/ijnhs.v2i2.88 - Anita Sukarno; Nur Hidayah; Musdalifah Musdalifah (International Journal of Nursing and Health Services (IJNHS), 2019)
Background: Diabetic foot ulcers were common diabetes complication that progressively growth globally. The effectivity of Manuka honey in the wound healing process was huge published currently. Modern dressing and Manuka honey may not affordable and cost-effective since these dressings were not produced originally in Indonesia. In addition, the published study of Indonesian honey is still lack. Therefore, we conducted this study to investigate the effectivity of Indonesian honey in diabetic foot ulcers healing process. Method: This study design was an observational case study. This study was conducted among type 2 diabetes with diabetic foot ulcers in Griya Afiat Homecare and ETN Center in Makassar City, Indonesia from March to June 2014. The Bates Wound Assessment Tool (BWAT) were used to collect the score of diabetic foot ulcer healing process regarding wound size, depth, edges, undermining, necrotic tissue type, necrotic amount, granulation, epithelization, exudate type and amount, surrounding skin color, edema and induration. Descriptive, Independent t-test, Analysis of Variance (ANOVA) and Wilcoxon signed rank test were conducted appropriately. Results: In total, 10 type 2 diabetes patients with diabetic foot ulcers were participated. The factors associated with wound healing process were diabetes treatment (t= 2.44, p= 0.041) and primary dressing (t= -2.76, p= 0.025). The effect of honey primary dressing was in reducing wound size (p= 0.043), improving necrotic tissue type (p= 0.041), reducing necrotic tissue amount (p= 0.042), increasing granulation (p= 0.038) and epithelization (p= 0.042). In the counterpart, the effect of modern dressing was in improving necrotic tissue type (p= 0.046) and increasing granulation (p= 0.042). Conclusion: Indonesian honey is beneficial on diabetic foot ulcers healing process. Recommendation: Therefore, findings suggest that honey should be considered as the alternative, cost effective and beneficial wound dressing on the diabetic foot ulcers.